Journal of Antitrust Enforcement Agency effectiveness study - Ezrachi, A; Kovacic, W; Hollman, H; Nowag, J; Ioannidou, M (Oxford University Press, 2016)
The Agency Effectiveness Study explores a wide range of the daily concerns faced by competition agency heads and their staff, with an emphasis on the formal and informal ways in which they are addressed. Managing and operating a competition agency is very much a process of learning-by-doing. The aim of the study is, therefore, to capture and make available the know-how that competition agency officials accumulate during their service. In particular, it aims to provide a candid account of the practical challenges encountered and solved by heads of agencies and their staff as they navigate through changing legal, social, political, and organizational landscapes.